Dynamics of Motivation Development in Second Phase of Primary School Age - I.Y. Kulagina; V.V. Golubev (Психолого-педагогические исследования)
The article presents the results of a study based on the principle of a longitudinal study, which reveals the dynamics of the development of educational motivation and broad social motivation in children. The study involved 44 children aged 9-10years (27 boys and 17 girls) who studied in the 3rd grade in the 2022-2023 academic year and in the 4th grade in the 2023-2024 academic year. In the study of motivation, the methods "The level of motivation of teaching" and "Subjective position", the method of motivational preferences "Goldfish" and the method "Golden Age" were used. It is shown that children at the end of primary school age are characterized by a combination of object and subject positions in relation to education; the changes occurring at this time in educational motivation are traced– a decrease in its level from 3rd to 4th grade. The relative stability of motivation with a broader social context has been established. There are only two trends – a weakening of "children's" desires (possession of things, toys, etc.) and an increased focus on achieving emotional and material well-being. The correlations between the indicators of educational and broad social motivation are revealed. In particular, a perspective and optimal subjective position in relation to education correlates with a focus on the future, the realization of one's goals, friendship with peers and concern for the well-being of the teacher.